Psychometric properties of the Chinese version of the Problem Areas in Diabetes scale (SG‐PAID‐C) among high‐risk polypharmacy patients with uncontrolled type 2 diabetes in Singapore - Siaw, Melanie Yee Lee (J Diabetes Investig, 2016)
AIMS/INTRODUCTION: Undetected diabetes distress is a cause of concern. However, the lack of a validated questionnaire is a barrier to screening for diabetes distress. The aim of the present study was to examine the validity and reliability of the Chinese version of the Problem Areas in Diabetes scale (SG‐PAID‐C), and its association with sociodemographic and clinical parameters in patients with type 2 diabetes. MATERIALS AND METHODS: This cross‐sectional study was carried out in four outpatient healthcare institutions in Singapore. Chinese‐speaking patients with uncontrolled type 2 diabetes, polypharmacy, and multiple comorbidities were administered the SG‐PAID‐C and European Quality of Life‐5 Dimensions questionnaires as quality of life measures. The factorial construct, convergent validity and internal consistency of SG‐PAID‐C were evaluated. RESULTS: The exploratory factor analysis resulted in a three‐factor structure of SG‐PAID‐C with subscales on emotional‐ and management‐related problem (11 items), ability to cope with diabetes problem (3 items) and support‐related problem (2 items). The findings also showed good model fit in the confirmatory factor analysis, and provided support for the construct and convergent validity of SG‐PAID‐C. Overall, the internal consistency of SG‐PAID‐C was good (Cronbach's alpha = 0.900). Sex and duration of diabetes were positively associated with the 16‐item SG‐PAID‐C, whereas age and type of antidiabetic agents were inversely associated with the 16‐item SG‐PAID‐C. CONCLUSIONS: The 16‐item SG‐PAID‐C is a valid and reliable instrument for use among patients with uncontrolled type 2 diabetes in Singapore. Future studies on its clinical utility should be carried out.